Bridging uncertainty: social support and health communication in assessing prospective ASD students for online learning - Purnamasari, Oktaviana; Firmansyah, Dwi (Frontiers in Communication, 2025)
The transition to online learning heightens uncertainty for prospective students with autism spectrum disorder (ASD), influencing their emotional readiness and academic adaptation. This study explores how assessment practices, strengthened by social support and health communication, help reduce that uncertainty. Using a qualitative case study design, the research examined institutional assessment practices at the London School Beyond Academy (LSBA) Jakarta, based on data collected that reflected the institution’s online admission and assessment procedures during the COVID-19 pandemic. The findings show that uncertainty often arose from ambiguous expectations, limited structured interaction, and unclear instructional procedures. LSBA’s online assessment combined interviews, behavioral observations, and structured online tasks while also considering parental involvement during sessions. Although challenges emerged (e.g., limited visibility of student behavior and the possibility of parental interference), structured protocols helped address these issues. The analysis demonstrates that social support (emotional, informational, and instrumental) and adaptive health communication strategies lower anxiety, strengthen resilience, and clarify expectations. The study contributes novelty by integrating the Uncertainty Reduction Theory (URT) with social support and health communication in the Indonesian context of online ASD assessments, an area rarely examined in current research. These findings suggest that integrating URT with social support and health communication offers a replicable model for inclusive assessment practices in digital education environments.